Electric cogeneration through gas turbine: a vision from the entrepreneurs in Manabí - Ulloa-de Souza, Raúl Clemente (2022)
The objective of this research article was the analysis of electric cogeneration through a gas turbine: a vision from the entrepreneurs in Manabí. Methodology: to achieve these objectives, a descriptive research was used, with a non-experimental design; the population was made up of 50 businessmen belonging to Manabi. There was no sample selection by virtue of the accessible and finite population. The techniques used were observation and survey and the questionnaire instrument with closed response options. Data analysis was performed through descriptive statistics. Results: 64% of businessmen use natural gas as an energy source, followed by biogas. 40% of entrepreneurs belonging to various industries use gas turbines, followed by the service sector (30%). The type of cogeneration technology is gas turbine (40%) followed by gas turbine and internal combustion. Conclusion: The use of gas turbines for power generation in entrepreneurs in Ecuador-Manabì has been acquiring growing importance, and it can be said that it is a relatively well-established technology. Cogeneration is a strategy that is more efficient than the production of electricity and heat separately.